Eksporterzy artykułów rolno-spożywczych z województwa warmińsko-mazurskiego wobec wyzwań rynku unijnego - Lizińska, Wiesława (Exporters of Agricultural and Food Products from Warmia and Mazury Voivodship in the Face of Challenges of the Union Market, 2005)
The integration with European Union gives new possibilities to selling agricultural and food products. It is caused by lifting restrictions in access to the European market. The aim of this paper is to show chosen problems of functioning enterprises which export agricultural and food products, what is the effect of integration and changes on the world market. Despite short time of the membership of Poland in the EU Polish exporters feel many results of this change (growth of export, broadening of choice, higher prices).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 25-30